Pemanfaatan Big Data dalam Meningkatkan Daya Saing UMKM - Muhammad Ridho Hasibuan; Wahyu Adriansyah; Zahri Akmal; Oktari Tarigan; Sahat Parulian Sitorus (Universitas Labuhanbatu, 2026)
The rapid development of information technology has driven the growth of data in massive volumes, commonly referred to as Big Data. The utilization of Big Data offers strategic opportunities for Micro, Small, and Medium Enterprises (MSMEs) to enhance their competitiveness amid increasingly intense business competition. This study aims to examine the role of Big Data in supporting decision-making, understanding consumer behavior, and improving the operational efficiency of MSMEs. The research method employed is a literature review of relevant journals, books, and research reports. The findings indicate that the application of Big Data enables MSMEs to conduct market analysis, personalize products, and optimize digital marketing strategies. However, challenges such as limited human resources, technological infrastructure, and data security remain significant barriers. Therefore, support from the government and related stakeholders is necessary to encourage the optimal adoption of Big Data in the MSME sector.